Microbial quality of herbal juices sold at sport complex in Washim - Kulkarni, Nikhilesh; Narwade, Jayshree; Pachori, Rachana; Sadar, Prithviraj (International Journal of Research in Medical Sciences, 2017)
Background: Herbal juices are gaining global attention due to their medicinal properties, nutritive and antioxidant activity. They are frequently consumed by the people of all age groups in the form of health drinks. However, many outbreaks of human infections have been reported to be associated with the consumption of contaminated herbal juices. Hence, microbial quality assessment of herbal juices is utmost important. Methods: The present study was undertaken to detect the existence of enteric pathogens as well as coliforms in the herbal juices sold at sport complex in Washim city area. The antimicrobial susceptibility testing was also performed to evaluate the MDR status of the isolates. Results: The results showed that most of the herbal juices are contaminated with Salmonella, Shigella and Coliforms. The pathogens were found to be multiple drug resistant strains which pose an alarming threat for the consumers. Conclusions: Regular monitoring of the quality of herbal juices for human consumption is recommended to avoid disease outbreak.